2019
DOI: 10.1002/lno.11165
|View full text |Cite
|
Sign up to set email alerts
|

Prey taxonomy rather than size determines salp diets

Abstract: Salps are gelatinous planktonic suspension feeders that filter large volumes of water in the food‐dilute open ocean. Their life cycle allows periodic exponential growth and population blooms. Dense swarms of salps have a high grazing impact that can deplete the photic zone of phytoplankton and export huge quantities of organic matter to the deep sea. Previous studies described their feeding manner as mostly nonselective, with larger particles retained at higher efficiencies than small particles. To examine sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 65 publications
(129 reference statements)
1
30
0
Order By: Relevance
“…LNA is largely associated with SAR11, the smallest and most abundant bacterial clade in the ocean ( Mary et al, 2006 ). These bacteria may slip through the mucus filter of tunicates ( Dadon-Pilosof et al, 2017 ; Dadon‐Pilosof et al, 2019 ) and evade filtration in many sponges ( Ribes et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…LNA is largely associated with SAR11, the smallest and most abundant bacterial clade in the ocean ( Mary et al, 2006 ). These bacteria may slip through the mucus filter of tunicates ( Dadon-Pilosof et al, 2017 ; Dadon‐Pilosof et al, 2019 ) and evade filtration in many sponges ( Ribes et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nishikawa and Tsuda (2001) quantified size‐fractionated chlorophyll concentrations in salp grazing incubation experiments and concluded that salp grazing rates were highest on 2–20 μ m prey. Dadon‐Pilosof et al (2019) found substantially higher S. maxima , Salpa fusiformis , and Thalia democratica grazing rates on picoeukaryotes and nanoeukaryotes than on Synechococcus , Prochlorococcus , and heterotrophic bacteria. Synechococcus has also been found in the fecal pellets of salps (Pfannkuche and Lochte 1993), although this does not necessarily imply efficient feeding on cyanobacteria‐sized cells, because mesozooplankton can also consume Synechococcus contained in aggregates (Stukel et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the broader prey size range of grazers feeding on large phytoplankton yields a steady-state prey biomass of lower average concentration at each size within that range than that for grazers of smaller phytoplankton. It is worth noting here that some grazers feed wholesale across the phytoplankton size domain (e.g., gelatinous tunicates feeding with mucous webs, 38,39 ) rather than in proportion to average prey size. Feeding by these organisms will positively tilt the phytoplankton SDS to a value between −4 and −3 in a 24 and (squares) unpublished data from the NAAMES program.…”
Section: Size Structuring Of Stable Phytoplankton Communitiesmentioning
confidence: 99%